Separação e identificação de constituintes químicos polares dos galhos de Porcelia Macrocarpa - Chaves, Mariana H.; Freitas, Alexander de; Roque, Nídia F.; Cavaleiro, Alberto José [UNESP] (Sociedade Brasileira de Química, 2000)
This paper describes a methodology to separate and identify polar compounds as flavonoid and lignan glucosides, amino acids, salt of quaternary ammonium amino acid and carbohydrates from branches of Porcelia macrocarpa (Annonaceae).
Separation and identification of polar constituents from the branches of Porcelia macrocarpa
Keywords: Porcelia macrocarpa; water-soluble compounds; Annonaceae